Past Directors present Gynecology and Obstetrics - Comité Editorial, - (2016)
Of the seven directors of the journal Obstetrics and Gynecology 2006 -from called Peruvian Journal of Gynecology and obstetrics, accompany us in the business of life Drs. Abraham Ludmir, Jorge Vidal and Jose Huaman, whom the Editorial Committee ago a souvenir of his time as Director of the Journal.